The role of brand equity in a new rebranding strategy of a private label brand - Marques, C. (2020)
The purpose of this study is to understand the effects of the rebranding process on private label performance output, namely, on brand equity. More specifically, the study aims to investigate the performance of brand equity constructs (brand awareness, brand associations, perceived quality and brand loyalty) before and after the rebranding process. A questionnaire was administered to 466 shoppers, who put forth their perceptions, of the brand’s image, before and after the rebranding. When analyzed altogether, brand equity constructs have not suffered significant changes, meaning that previously existing brand equity had successfully been transferred onto the new brand; however, new brand equity was not created in the process. Consumers do still associate the private label brand image with its previous brand identity. Nevertheless, their ability to easily identify the various brand tiers was improved with the new image. Consumers associate the rebranded image with being “innovative” and “original” and describe the previous image as “inexpensive” and “trustworthy”. Brand awareness and loyalty are the factors that relate the most to consumers’ perceptions of the brand before its rebranding. This study contributes to the brand management literature by providing a new look into the under-researched problem of rebranding and brand equity, empirically validating the real-life market case.